Effects of retrieval practice and presentation modality on verbal learning: testing the limits of the testing effect. Issue 8 (14th September 2019) - Wilkinson, Aimee M.; Hall, Amanda C. G.; Hogan, Eileen E.
ABSTRACT: The testing effect refers to improved memory after retrieval practice and has been researched primarily with visual stimuli. In two experiments, we investigated whether the testing effect can be replicated when the to-be-learned information is presented auditorily, or visually + auditorily. Participants learned Swahili-English word pairs in one of three presentation modalities – visual, auditory, or visual + auditory. This was manipulated between-participants in Experiment 1 and within-participants in Experiment2. All participants studied the word pairs during three study trials. Half of participants practiced recalling the English translations in response to the Swahili cue word twice before the final test whereas the other half simply studied the word pairs twice more. Results indicated an improvement in final test performance in the repeated test condition, but only in the visual presentation modality (Experiments 1 and 2) and in the visual + auditory presentation modality (Experiment 2). This suggests that the benefits of practiced retrieval may be limited to information presented in a visual modality.